Changing Pattern and Drivers of Land Use and Land Cover in Bagmati Province of Nepal - Rimal, Bhagawat; Paudel, Basanta; Rijal, Sushila; Pangali Sharma, Til Prasad; Pandey, Pramod (Himalayan Review, 2024)
Land use and land cover (LULC) represents the physical component of the Earth’s environment, and often changes as a result of natural and anthropogenic activities. This study carried out changing patterns and orientations of LULC types of Bagmati province of Nepal by using satellite images between 1996 and 2016. The study applied a classification scheme through support vector machines (SVM) for the period from 1996 to 2006, and 2006 to 2016. Our study explored that built-up area expansion was the major change witnessed which increased from 85.25 km2 in 1996 and sharply increased and labeled 250.06 km2 in 2016. Similarly, the forest land of the province increased by 329.02 km2 between 1996 and 2016. The status of cultivated land was found slightly decreasing trend, which was noted at 6113.50 km2 in 1996 and labeled at 5725.82 km2 in 2016. The shrubland of the province declined by 272.03 km2 from 1851.67 km2 in 1996 to 1579.64 km2 in 2016. However, the status of snow/ ice cover found at fluctuated form, which was noted 774.27 km2 in 1996, 1297.43 km2 in 2006, and 828.92 km2 in 2016. The increasing population trend is the main driver of the high rate of built-up area expansion and contraction of the cultivated land. Community forestry programs highly supported the expansion of forest cover. The proper implementation and improvement of the existing policy are the major concerns for sustainable LULC management in the province.